1976
DOI: 10.1111/j.1600-0528.1976.tb00974.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent aphthous ulcerations in a mixed Arab community

Abstract: Twenty thousand Arabs of various nationalities living in Kuwait have been investigated over the past 5 years; 5,470 (27 %) manifested recurrent aphthous ulcerations (RAU). Non‐Kuwaiti Arabs were affected more than Kuwaitis and the prevalence of the disease was respectively 35% and 18 %. Among Kuwaitis, only 5 % of the Bedouins manifested the disease whereas 22 % of urbanized Arabs were affected. The ratio of the affected females to males in this study was 6:5. The clinical course of RAU in Arabs was similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Population studies have found RAS in about 2% of Swedish (Axell and Henricsson, 1985b), 1.9% of Spanish (Garcia‐Pola Vallejo et al , 2002) and 0.5% of Malaysian (Zain, 2000) examined adults, although 17.7% of Swedish and 9.7% of adults in Ljubljana (Slovenia) (Kovac‐Kovacic and Skaleric, 2000) have a history of possible RAS. RAS seems to be infrequent in Kuwaiti Bedouins (5%; Fahmy, 1976) and it has been found in only 0.1% of Indians in Malaysia (Zain, 2000). However, RAS may be especially common in North America (Embil et al , 1975).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Population studies have found RAS in about 2% of Swedish (Axell and Henricsson, 1985b), 1.9% of Spanish (Garcia‐Pola Vallejo et al , 2002) and 0.5% of Malaysian (Zain, 2000) examined adults, although 17.7% of Swedish and 9.7% of adults in Ljubljana (Slovenia) (Kovac‐Kovacic and Skaleric, 2000) have a history of possible RAS. RAS seems to be infrequent in Kuwaiti Bedouins (5%; Fahmy, 1976) and it has been found in only 0.1% of Indians in Malaysia (Zain, 2000). However, RAS may be especially common in North America (Embil et al , 1975).…”
Section: Epidemiologymentioning
confidence: 99%
“…There may be female predominance of RAS in adults (Ship, 1972; Fahmy, 1976; Axell and Henricsson, 1985b; Pongissawaranun and Laohapand, 1991; Donatsky, 1973; Kovac‐Kovacic and Skaleric, 2000) and in children (Field et al , 1992; Kleinman et al , 1994). In the USA, white people are three times more frequently affected than black people (Kleinman et al , 1994).…”
Section: Epidemiologymentioning
confidence: 99%
“…Recurrent aphthous stomatitis (RAS) is a distinct oral condition of unknown aetiology characterised by the spontaneous emergence of more than two bouts of oral ulcers per year, not associated with ulcers elsewhere in the body or with an underlying systemic abnormality. RAS is a common oral ulcerative disease in many parts around the world . It is usually a diagnosis by exclusion after careful consideration of the patient's history and clinical appearance of the disease .…”
Section: Introductionmentioning
confidence: 99%
“…Não há predileção por sexo, condição socioeconômica ou raça (CASIGLIA, 2002). Alguns autores referem uma discreta predominância no sexo feminino (FAHMY, 1976;MILLER;SHIP;RAM, 1977), aumento na incidência e severidade de UAR em indivíduos de classes socioeconômicas mais elevadas (SHIP, 1972), e maior freqüência em indivíduos da raça branca na população adulta dos EUA (RIVERA-HIDALGO; SHULMAN; BEACH, 2004).…”
Section: Epidemiologiaunclassified